A study on the outcome of displaced midshaft non-comminuted clavicle fractures treated with anatomical locking plate versus titanium elastic nail - Vineet Thomas Abraham; Chandrasekaran Marimuthu (Journal of Orthopaedics, Trauma and Rehabilitation)
Purpose: Fixation of displaced midshaft clavicle is well known to decrease nonunion, malunion and shoulder disability as compared to nonoperative treatment. This study was done to compare the clinical and functional outcome of group 1 clavicle fractures treated with anatomic locking plates (ALP) versus Titanium elastic nail (TEN). Methods: We studied patients presenting with displaced midshaft clavicle fractures treated with ALP or TEN. The study period was from Jan 2013 to Dec 2016. Patients were reviewed and at each visit clinical and radiological progress of union was noted, complications if any were noted, functional assessment was done using the quick Dash score and Constant Murley score. Results: A total of 116 patients met our inclusion criteria. 62 patients were treated with TEN and 54 with ALP. Bony union was achieved at an average of 11.8 weeks in the TENS group and 12.8 weeks in the ALP group post operatively and this was found to be significant. The mean postoperative Constant Murley score in the ALP and the TEN groups were 92.8 (range 80–97), and 93.7 (82–97) respectively. The mean postoperative quick dash score in the ALP and TEN groups were 2.48(range from 0 to 6.8) and 2.1 (range 0–9.1) respectively. Conclusion: Both Anatomical locking plate and TEN are good options for the treatment of non-comminuted mid clavicular fractures as they have a similar functional outcome. TEN nail insertion has the advantage of being minimally invasive, having a faster union time and may be recommended in midshaft clavicle fractures without comminution.